A Molecular Cable Car for Transmembrane Ion Transport. Issue 13 (20th February 2019) - Credi, Alberto
Abstract: The controlled transport of molecular and ionic substrates across bilayer membranes is a fundamental task for the operation of living organisms. It is also a highly fascinating and demanding challenge for artificial molecular machines. The recent report of a synthetic transmembrane molecular shuttle that can transport potassium ions selectively down a gradient in a liposomal system makes a small but significant step towards this goal. Abstract : Thanks for the lift, mate ! A molecular machine based on a rotaxane embedded in a lipid bilayer can carry potassium ions across the membrane by taking advantage of the stochastic shuttling motion of its macrocyclic ring.